Boosting the Redox Kinetics of High‐Voltage P2‐Type Cathode by Radially Oriented 010 Exposed Nanoplates for High‐Power Sodium‐Ion Batteries. Issue 1 (29th October 2021) - Li, Feng; Fan, Ke; Hou, Peiyu; Huang, Haitao
Abstract : High‐voltage P2‐type cathode with large capacity, high air stability, and low cost has attracted extensive attention. However, large ionic radius of Na + and Na + /vacancy ordering result in low reaction kinetics and poor high‐rate capability. Herein, cobalt‐doped hierarchical structure assembled by radially oriented 010 exposed nanoplates is developed. With radially oriented grains infiltrating from surface to interior, all the 010 exposed surfaces are electrochemically active planes, and Na + ions diffuse directly into electrolyte without passing through grain boundaries, building up 3D transfer channels. The trivalent cobalt substitution suppresses unwanted Na + /vacancy ordering and increases energy barrier of the phase transition from P2‐ to O2‐type oxide. These synergetic effects remarkably boost the redox kinetics of high‐voltage P2‐type cathode. Consequently, a large reversible capacity of 112 mAh g −1 is achieved even at 20 C, indicating excellent high‐rate capability. The absence of P2–O2 phase transition also gives rise to superior cycling stability, maintaining a capacity retention of 85% after 200 cycles. In addition, full cells composed of this hierarchical P2‐type cathode and hard carbon anode deliver high energy‐ and power‐densities. These achievements offer a new insight into boosting redox kinetics of P2‐ and O3‐type layered cathodes for high‐power sodium‐ion batteries. Abstract : The cobalt‐doped hierarchical structure assembled by radially oriented 010 exposed nanoplates is proposed to boost the redox kinetics of P2‐type layered cathodes for high‐power sodium‐ion batteries.